Chronic caffeine consumption curbs rTMS-induced plasticity - Vigne, Megan; Kweon, Jamie; Sharma, Prayushi; Greenberg, Benjamin D.; Carpenter, Linda L.; Brown, Joshua C. (Frontiers in Psychiatry, 2023)
Background: Caffeine is a widely used psychostimulant. In the brain, caffeine acts as a competitive, non-selective adenosine receptor antagonist of A1 and A2A, both known to modulate long-term potentiation (LTP), the cellular basis of learning and memory. Repetitive transcranial magnetic stimulation (rTMS) is theorized to work through LTP induction and can modulate cortical excitability as measured by motor evoked potentials (MEPs). The acute effects of single caffeine doses diminish rTMS-induced corticomotor plasticity. However, plasticity in chronic daily caffeine users has not been examined. Method: We conducted a post-hoc secondary covariate analysis from two previously published plasticity-inducing pharmaco-rTMS studies combining 10-Hz rTMS and D-cycloserine (DCS) in twenty healthy subjects. Results: In this hypothesis-generating pilot study, we observed enhanced MEP facilitation in non-caffeine users compared to caffeine users and to placebo condition. Conclusion: These preliminary data highlight a need to directly test the effects of caffeine in prospective well-powered studies, because in theory, they suggest that chronic caffeine use could limit learning or plasticity, including rTMS effectiveness.